Successful anesthesia case of emergency cesarean section complicated with pregnancy-related group: A streptococcus sepsis - Yuta Kawatsu; Mitsunori Miyazu; Taiki Kojima (Journal of Obstetric Anaesthesia and Critical Care, 2022)
Pregnancy-related Group A streptococcus (GAS) sepsis is a rare, rapidly progressing life-threatening disease. Previous reports described the clinical features of pregnancy-related GAS sepsis, however, the evidence regarding general anesthesia is extremely limited. This report aims to alert anesthesiologists that pregnancy-related GAS sepsis is an emerging life-threatening disease and to describe the clinical issues when performing general anesthesia in the emergency cesarian section. We describe the case of a 37-year-old pregnant woman with undiagnosed pregnancy-related GAS sepsis who exhibited rapid, progressive circulatory collapse. Attentive anesthesia management and smooth transition to the cesarean section resulted in saving both the mother and baby without any complications. The evidence regarding anesthesia management in pregnancy-related GAS sepsis is extremely lacking. To make the diagnosis of GAS sepsis before initiating the emergency cesarean section was challenging under rapid deterioration. Anesthesiologists should consider GAS sepsis in pregnancy with aggressive septic features and prepare for the fatal intraoperative complications during general anesthesia.